2008
DOI: 10.1007/s00395-008-0733-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammatory cytokines in endothelial dysfunction

Abstract: Clinical and experimental data support a link between endothelial dysfunction and inflammation. Inflammatory cytokines are important protagonists in formation of atherosclerotic plaque, eliciting effects throughout the atherosclerotic vessel. Importantly, the development of atherosclerotic lesions, regardless of the risk factor, e.g., diabetes, hypertension, obesity, is characterized by disruption in normal function of the endothelial cells. Endothelial cells, which line the internal lumen of the vasculature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
289
1
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(311 citation statements)
references
References 74 publications
4
289
1
17
Order By: Relevance
“…This study included multiple biomarkers of inflammation and endothelial dysfunction, including CRP, sICAM-1, sE-selectin and angiotensin II; of the four, CRP, sICAM-1 and sE-selectin reflect the status of inflammation or the status of endothelial dysfunction. [25][26][27] In addition to its role as a vasoconstrictor, angiotensin II induces endothelial dysfunction and inflammation, resulting in accelerated progression of atherosclerosis. 28,29 Our study found that IR was related to the biomarkers of inflammation and endothelial dysfunction, both in subjects with hypertension and those without hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…This study included multiple biomarkers of inflammation and endothelial dysfunction, including CRP, sICAM-1, sE-selectin and angiotensin II; of the four, CRP, sICAM-1 and sE-selectin reflect the status of inflammation or the status of endothelial dysfunction. [25][26][27] In addition to its role as a vasoconstrictor, angiotensin II induces endothelial dysfunction and inflammation, resulting in accelerated progression of atherosclerosis. 28,29 Our study found that IR was related to the biomarkers of inflammation and endothelial dysfunction, both in subjects with hypertension and those without hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators clearly demonstrated that inflammatory mediators induced endothelial dysfunction. 43 Qamirani et al 44 reported that CRP inhibits endothelium-dependent NOmediated dilation in coronary arterioles by producing superoxide from NAD(P)H oxidase through p38 kinase activation. The present study demonstrated that olmesartan significantly reduced serum hsCRP levels as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…AS is a commonly recognized inflammatory disease [2][3][4] , although the mechanism of its initiation and progression is not fully understood.…”
Section: Introductionmentioning
confidence: 99%